Hadde döküm yöntemiyle Al-Si kaynak teli üretimi - Eroğlu, Mehmet; Kurt, Bülent; Güler, S. Hale; Guler, Omer; Özel, Serkan; Kerküt, Erhan; Kürüm, Murat (My University, 2007)
-
01.09.2007
Keywords: Metalürji Mühendisliği